Kinematics Analysis and Simulation of Line-driven Hedge Trimming Manipulator - Xue Zan; Luo Tianhong; Chen Cai (Jixie chuandong)
Aiming at the problem that hedge manipulators can’t work in complex and unstructured environments, a redundant line-driven hedge trimming manipulator with stronger environmental adaptability, higher degree of freedom and larger workspace is proposed. The kinematics model of single joint is established by coordinate analysis method, and the mapping relationship between rope length and joint rotation angle is solved. The forward kinematics mathematical model of 10-DOF manipulator is analyzed based on D-H parameter method. The inverse kinematics of redundant manipulator is studied by genetic algorithm, and the inverse kinematics of redundant manipulator is solved. The simulation results show that the genetic algorithm has high accuracy and fast solution. The coupling between the joints and ropes of the manipulator is analyzed and the decoupling formula is deduced. The correctness of forward and inverse kinematics model and decoupling model of the manipulator are verified by simulation, which lays a foundation for the control and trajectory planning of the rope-driven redundant manipulator.